Evidence for morphological and genetic structuring of Plebeia flavocincta (Apidae: Meliponini) populations in Northeast Brazil - Maia, Ulysses Madureira; Santos Júnior, José Eustáquio dos; Molina, Michele; Galaschi-Teixeira, Juliana Stephanie; Carvalho, Airton Torres; Miranda, Leonardo de Sousa; Imperatriz-Fonseca, Vera Lucia; Oliveira, Guilherme; Giannini, Tereza Cristina (Frontiers in Ecology and Evolution, 2022)
Tropical dry forests are increasingly threatened by human activities. In Northeast Brazil, the Caatinga, an area of tropical dry forests surrounded by wetlands, is considered globally unique among these habitats. In this region, the stingless bee Plebeia flavocincta is found in a variety of environmental, ecological, and demographic conditions. We aimed to characterize P. flavocincta populations within its natural range through wing geometric morphometrics and mitochondrial DNA analyses. The characterization of population variability can clarify whether the species is morphologically and genetically diverse and whether populations are morphologically and genetically structured. We analyzed 673 samples by wing morphometry and 75 by cytochrome-b assays. Our results revealed P. flavocincta is genetically and morphologically diverse and populations are morphologically and genetically structured. Despite the differentiation between the two most morphologically distant populations, we verified a large overlap of morphological variation between all populations. The genetic analysis showed that the haplotypes were geographically structured into six clusters, four of which were located in coastal areas, and the remaining two in the drier inland region. The characterization of P. flavocincta populations is an important step toward decision-making in programs for the protection, management, and sustainable use of this stingless bee in local breeding efforts.